The WTO, Developing Countries and the Doha Development Agenda 2004
DOI: 10.1057/9780230523265_4
|View full text |Cite
|
Sign up to set email alerts
|

OECD Domestic Support and Developing Countries

Abstract: This paper aims to shed light on the potential interests of developing countries in reforms to domestic support for agriculture in the OECD economies. In order to accomplish this goal, we begin by reviewing the literature on the impacts of domestic support on key variables, including farm income, in the OECD economies themselves.We then proceed to revise the standard GTAP model of global trade, based on recent work at the OECD, in order to better capture these impacts. This work at OECD and analytical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…As stabilising farm income is the key U Un ni iv ve er rs si it ty y o of f P Pr re et to or ri ia a e et td d --G Ge eb br re eh hi iw we et t, , Y Y F F ( (2 20 00 04 4) ) objective of the agricultural policy in OECD countries (OECD, 2002b), the PEM result suggests that payment support based on land and historical entitlement will offer large efficiency in income transfer and yield minimum trade distortions. Based on these findings and using GTAB 5 version that captures the disaggregated domestic support, Dimaranan, Hertel, and Keeney (2003) simulated three different scenarios to analyse the impact of a cut in domestic support by OECD countries on the welfare of developing countries.…”
Section: Domestic Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…As stabilising farm income is the key U Un ni iv ve er rs si it ty y o of f P Pr re et to or ri ia a e et td d --G Ge eb br re eh hi iw we et t, , Y Y F F ( (2 20 00 04 4) ) objective of the agricultural policy in OECD countries (OECD, 2002b), the PEM result suggests that payment support based on land and historical entitlement will offer large efficiency in income transfer and yield minimum trade distortions. Based on these findings and using GTAB 5 version that captures the disaggregated domestic support, Dimaranan, Hertel, and Keeney (2003) simulated three different scenarios to analyse the impact of a cut in domestic support by OECD countries on the welfare of developing countries.…”
Section: Domestic Supportmentioning
confidence: 99%
“…Since the policy reinstitution (changing the composition of domestic support) is likely to be accepted politically in OECD countries (as farm income is maintained), Dimaranan et al, (2003) concluded that developing countries' main focus should be improving market access (reduction of tariff barriers). Moreover, they recommend that as long as domestic support measures remains decoupled, developing countries should permit the OECD countries to augment domestic support.…”
Section: Domestic Supportmentioning
confidence: 99%
“…Dimaranan et al (2003) work out the average trade specialization indices for several countries and regions over the course of three decades (1965-1975, 1976-1985, and 1986-1998). Tropical products are predominantly produced in DCs, while temperate products are produced in developed countries as well.…”
Section: Trade In Tropical Agricultural Productsmentioning
confidence: 99%
“…Developed countries' share of world trade in manufactures has fallen from 90 per cent in 1970 to 72 per cent in 2000 (World Bank, 2002). 4 Estimates of the downward impact on world prices caused by OECD domestic support are between 3.5 and 5 per cent for many agricultural commodities including wheat & other coarse grains and oilseeds (Dimaranan et al, 2003). 5 According to their estimates, Latin America and the Caribbean lose about US$8.3 billion in annual income from agriculture, Asia loses some US$6.6 billion, and sub-Saharan Africa close to US$2 billion.…”
Section: Introductionmentioning
confidence: 99%